Full-scale testing to evaluate the performance of standing seam metal roofs under simulated wind loading. (15th December 2015) - Habte, Filmon; Asghari Mooneghi, Maryam; Gan Chowdhury, Arindam; Irwin, Peter
Highlights: Roof profile and eave details highly affect suction on standing seam metal roofs. ASCE 7–10 might produce unconservative results in trapezoidal standing seam roofs. Trapezoidal roofs experience higher suction and deflections than vertical-leg roofs. ASTM E1592 produces conservative results. Wind-induced vibrations in WOW produced different failure mode from ASTM E1592 tests. Abstract: The current methods for evaluating the adequacy of metal roofs in withstanding wind-induced loads involve undertaking uniform uplift pressure tests. These methods may not be truly representative of real conditions, and might set higher minimum design requirements than necessary in some cases, and in others they could underestimate effects of very localized peak pressures. This research work presents results of a full-scale experimental study conducted under more realistic wind loading with the panels installed as they would be in the American Society for Testing and Materials (ASTM) E1592 test chamber. The research objectives were to (i) measure the uplift roof pressure experience by mono-sloped standing seam metal roofs and compare them with the provisions of the American Society of Civil Engineers (ASCE) 7–10 standard, (ii) evaluate the performance of standing seam roofs under high winds, and (iii) compare the deflections and failure modes observed under more realistic wind loading to uniform loading tests. The research has provided test based data on aerodynamic loading of two types of standing seam metal roofs (i.e. vertical-leg and trapezoidal), as well as their performances under high wind speeds. Significantly higher pressure was recorded on the trapezoidal roof. This showed that roof panel profile and perimeter eave attachments can significantly affect uplift pressures. The ASCE 7–10 standard was observed to underestimate corner wind suctions on trapezoidal roof. Lower deflections were recorded by the vertical-leg roof owing to its higher stiffness and lower suctions experienced. The ASTM E1592 test protocol was observed to produce higher deflections and more conservative failure wind speeds than those experienced in the current tests. However, entirely different failure modes were observed between the uniform and dynamic tests. This was attributed to wind-induced vibrations that were observed in the current tests that are not present in the ASTM E1592 test, which is entirely static. The current research results may suggest future directions to enhance the existing testing standards.